Gingival spheroids possess multilineage differentiation potential. Issue 3 (5th June 2017) - Subbarayan, Rajasekaran; Murugan Girija, Dinesh; Ranga Rao, Suresh
Abstract : Recently studies have demonstrated HGMSCs as ideal candidates for regenerative study. Interestingly we found that HGMSCs derived spheroids are more potent and maintain the properties of stemness convincingly compared to conventional culture methods. During the culture, GMSCs instinctively accumulated into spheroids and display multipotent STRO‐1 and Vimentin‐positive cells. Reduced phenotypic expression of CD73, CD105, and elevated expression STRO‐1 and CD‐34. Pluripotent nature of S‐GMSCs putatively shown the expression of OCT4A, NANOG, SOX‐2, SSEA4, TRA‐1‐60, and TRA‐181. Also, levels of protein are much higher in spheroid than dissociated culture. On endothelial induction, spheroid differentiated and developed a vascular structure with positive expression of CD31 and on neuronal induction showed positivity for TUJ1 and E‐Cadherin. Importantly, undifferentiated state of S‐GMSCs exhibited significant upregulation of aforementioned pluripotent genes and lack of pro‐inflammatory cytokines IL‐6 and amplified ARF signal confirming that the spheroids are not teratoma formation. However, higher of CAP1, CP, TGFβ, OPN, PPARɣ, TUJ1, and NESTIN expression observed in spheroids, and minimal expression of the same markers were observed in adherent GMSCs respectively. Ahead of dissociated gingival culture, spheroid provides enhanced viable, pluripotent, and multilineage ability. This study suggested that S‐GMSCs increased the chances of therapeutic efficacy in the regenerative applications. Abstract : This study suggested that Spheroid‐GMSCs increased the chances of therapeutic efficacy in the regenerative applications.